(untitled) (Imaginations: Journal of Cross-Cultural Image Studies, 2014)
By drawing upon Siegfried Kracauer’s concept of cinema as a “mirror” of society, this article explores the impact of the “terror years” since 2001 on US cinema. Hollywood was the main cultural apparatus for coping with 9/11, which had left Americans struggling in the “desert of the real” (Žižek). Visual content simplifies traumatic events like the terrorist attacks for audiences—often expressing them in simple Manichean black and white terms and thereby offering moral guidance, unity, and a sense of destiny. Hollywood’s response to 9/11 included all these different aspects: It appealed to an “unbroken” spirit, strove to reassert the symbolic coordinates of the prevailing American reality, and mobilised for a response to new challenges. With time passing, Hollywood also incorporated the mounting doubts and dissent associated with this process. As the review of relating movies of the “terror years” demonstrates, the American film industry has examined, processed, and interpreted the meaning of the terrorist attacks in great variety: Ranging from merely atmospheric references to re-enactments, from pro-war propaganda to critical self-inquiry.